Penerapan Analisis SWOT dalam Meningkatkan Kinerja Karyawan di STMIK Widuri - Aprilia Fida Nurlita (Politeknik Kampar, 2024)
This study aims to analyze the application of SWOT analysis (Strengths, Weaknesses, Opportunities, Threats) in improving employee performance at STMIK Widuri. In the context of educational organizations, employee performance is a crucial factor that can impact service quality and the achievement of institutional goals. Therefore, SWOT analysis is used to identify the strengths, weaknesses, opportunities, and threats that affect employee performance within the STMIK Widuri environment. This research uses a qualitative approach with a case study method, involving interviews and direct observations with several employees and management at STMIK Widuri. The results indicate that the implementation of SWOT analysis can help the organization identify internal strengths that can be maximized, such as employee skills and experience, as well as adequate infrastructure. On the other hand, weaknesses found, such as the lack of training and competency development, can be addressed by designing more structured training programs. Opportunities for improving employee performance, such as utilizing information technology, can also be maximized. Meanwhile, external threats, such as competition between educational institutions, can be mitigated by enhancing collaboration and innovation in teaching. Overall, the findings suggest that the application of SWOT analysis at STMIK Widuri can make a significant contribution to improving employee performance through the identification of appropriate strategies to face challenges and take advantage of available opportunities. It is hoped that the results of this study will serve as a reference for the development of policies and human resource strategies at higher education institutions.